2022
DOI: 10.1002/1873-3468.14433
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide action in the regulation of plant autophagy

Abstract: Hydrogen sulfide is a signalling molecule with a well‐established impact on both plant and animal physiology. Intense investigation into the regulation of autophagy by sulfide in Arabidopsis thaliana has revealed that the post‐translational modification of persulfidation/S‐sulfhydration plays a key role. In this review focused on plants, we discuss the nature of the sulfide molecule involved in the regulation of autophagy, the final outcome of this modification and the persulfidated autophagy proteins identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 87 publications
1
4
0
Order By: Relevance
“…4 ) and protein ubiquitination ( Fig. 5 ) induced by drought in a similar way as previously demonstrated when autophagy is induced by other situations ( Aroca and Gotor, 2022 ).…”
Section: Discussionsupporting
confidence: 84%
“…4 ) and protein ubiquitination ( Fig. 5 ) induced by drought in a similar way as previously demonstrated when autophagy is induced by other situations ( Aroca and Gotor, 2022 ).…”
Section: Discussionsupporting
confidence: 84%
“…AP39, an H 2 S donor, induces stomatal closure in a complex IV-dependent manner in Arabidopsis thaliana [ 64 ]. H 2 S at high concentration inhibits complex IV, and the inhibitory effect on complex IV contributes to the toxicity of H 2 S in plants [ 110 , 111 ].…”
Section: The Regulation Of Mitochondrial Function By H 2 ...mentioning
confidence: 99%
“…Hydrogen sulfide (H 2 S) is a key gasotransmitter in plants that affects numerous enzymatic pathways within, and between cells, and the addition of exogenous H 2 S often has a strong positive effect at surprisingly low doses on maize, soybean, wheat, cucumber, peas, tomatoes, broccoli, lettuce, sugar beets, strawberries, radishes, and kiwi plants. , H 2 S is produced in cells and found at nanomolar concentrations, and recent work has shown that applying exogenous H 2 S to plants has dramatic effects, including increasing their overall size and mass, protection from high salt concentrations, protection from heat and drought stress, increased root growth, and prolonged shelf life of harvested crops. ,,, For example, the addition of exogenous H 2 S to plants such as over a dozen different plants increases their ability to withstand salt stress. , Although the process by which exogenous H 2 S enables plants to survive salt stress is complex, it has been shown to increase the activity of antioxidant enzymes, affect the levels of Na + in cells, and regulate several signaling proteins. The importance of exogenous H 2 S in agriculture has been established, and many current studies investigate the fundamental biochemistry of H 2 S within plants and how to apply H 2 S in a safe, dependable manner . Most of the early work in this field used micro to millimolar concentrations of aqueous H 2 S delivered once or twice daily.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen sulfide (H 2 S) is a key gasotransmitter in plants that affects numerous enzymatic pathways within, and between cells, 1 10 and the addition of exogenous H 2 S often has a strong positive effect at surprisingly low doses on maize, soybean, wheat, cucumber, peas, tomatoes, broccoli, lettuce, sugar beets, strawberries, radishes, and kiwi plants. 6 , 11 24 H 2 S is produced in cells and found at nanomolar concentrations, and recent work has shown that applying exogenous H 2 S to plants has dramatic effects, including increasing their overall size and mass, protection from high salt concentrations, protection from heat and drought stress, increased root growth, and prolonged shelf life of harvested crops.…”
Section: Introductionmentioning
confidence: 99%